Spontaneous coronary artery dissection: an Italian single centre experience. Issue 2 (February 2022) - Solinas, Emilia; Alabrese, Renato; Cattabiani, Maria Alberta; Grassi, Francesca; Pelà, Giovanna Maria; Benatti, Giorgio; Tadonio, Iacopo; Toselli, Marco; Ardissino, Diego; Vignali, Luigi
Abstract : Aims: Spontaneous coronary artery dissection (SCAD) is an emerging cause of acute myocardial infarction (AMI) in young women without a typical cardiovascular risk profile. Knowledge on SCAD is based on observational studies and is still scarce. The aim of this monocentric observational study was to evaluate the predisposing factors, clinical features and prognosis of SCAD patients. Methods: Between 2013 and 2020, 58 patients with angiographic diagnosis of SCAD were identified in our centre with an overall prevalence of 0.9% among patients admitted for AMI (58 of 6414 patients). Results: The mean age was 54 ± 11 years and the majority were women ( n = 50, 86%) with one or fewer cardiovascular risk factors ( n = 35, 60%). The prevalence of Fibromuscolar Dysplasia (FMD) was 39% (7 of 18 screened patients). The rate of major adverse cardiovascular and cerebrovascular events (MACCEs) was used to assess the prognosis. Out-of-hospital cardiac arrest because of ventricular fibrillation was observed in four (7%) patients. The majority of patients ( n = 51, 88%) were treated conservatively without revascularization. The in-hospital and 30-day clinical course was uneventful in most patients ( n = 54, 93%) with two cardiac deaths. During a median follow-up of 12 months, there were no further deaths. The global rate of SCAD recurrence was significant ( n = 8, 14%) but predictors have not been identified. Conclusion: Although overall survival seems good, SCAD is a potentially malignant, not rare disease, which can present with sudden cardiac death and not uncommon recurrence. Prognostic stratification and optimal management of SCAD patients remain to be defined.